Propolis influence on erythrocyte membrane disorder (hereditary spherocytosis): a first approach - Moreira, Leandro L. (2015)
Propolis is a resinous substance collected from plants by bees. Its composition depends on the vegetation, the season, and the source area. It usually contains many chemical compounds such as polyphenols, steroids and amino acids. The hereditary spherocytosis (HS) is a type of anaemia characterized by microcytic and hyperchromic red cells, spherical in shape and without central pallor. Clinically, subjects present from asymptomatic conditions to severe haemolytic anaemia. In this study it was evaluated the effect of two propolis extracts in the osmotic fragility of HS patient red blood cell (RBC) membrane. It was found that propolis decreases the erythrocytes membrane fragility, being the effect of Bornes propolis more pronounced than Fundao propolis'. This effect was related with the higher phenolic content of the former propolis. The results obtained in vitro suggest that the membrane fragility increases under oxidative stress conditions for the patient RBC's and the protection effect of propolis is due to its antioxidant properties. These results open doors for future investigations in order to elucidate the mechanisms, identify the main compounds involved in this fragility protection of the erythrocyte membrane. This is the first work reporting an evaluation of the propolis effect in a blood disease. (C) 2010 Elsevier Ltd. All rights reserved.